ANALYSIS OF GROUPER (Ephinephelus spp.) EXPORT CONTRIBUTION TO OWN-SOURCE REVENUE SOUTH SULAWESI PROVINCE - Sutinah Made; Sitti Fakhriyyah; Andi Darawelalangi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
This study aims to Determine the exsports contribution of groupers against region income in south Sulawesi and determine the contribution of groupers the next fiveyears against region income in South Sulawesi. This research was conducted during two months on May to June in Fish Quarantine, Handling Quality and Safety of Fishery products in South Sulawesi. The method used is secondary data analysis is sets (search-discover) the source data/information including, Fish Quarantine, Handling Quality and Safety of Fishery products of Marine nd Fisheries Agency of South Sulawesi, then collect data already available (within the document) as well as normalize the data if needed and possible (make data from various sources be equal in the same shape). The data used is primary data and secondary data, primary data obtained from interview by Hall of the information field quarantine quality handling fish and Fishery and safety findings from marine and fisheries department staff in South Sulawesi Province about information PNBP export of grouper. Secondary data were obtained from Quarantine Fish, Quality Control and Safety of Marine and Fisheries Agency in South Sulawesi. Based on this research grouper export contrinution to the South Sulawesi Regional Revenue an average of 32% annually and in 2015 obtained the highes contribution in 63 % and the contribution of groupers expors in the next five years in 2020 for region income in South Sulawesi is Rp 507.600.000,-. Key words : Export, Grouper, Region Income, Contribution